Utilizing Scramble Words Technique to Enhance Students’ Vocabulary Mastery - Puspa Natasya; Mashuri Mashuri; Andi Patmasari; Mochtar Marhum (MASI Mandiri Edukasi, 2026)
Vocabulary mastery is a fundamental component of English language learning. Nevertheless, many junior high school students encounter difficulties due to monotonous instructional methods. This study aimed to investigate the effect of the Scramble Words technique on vocabulary mastery among eighth-grade students. Using a quantitative quasi-experimental design, the study involved 61 eighth-grade students from SMP Negeri 7 Palu, who were divided into an experimental and a control group. Data were collected through a vocabulary pretest and posttest focusing on nouns, verbs, adverbs, and adjectives. The experimental group was instructed using the Scramble Words technique, whereas the control group received conventional teaching. Based on the analysis, the experimental group showed superior gains in vocabulary mastery compared to the control group. This difference was statistically significant, as evidenced by the t-test, which showed that the calculated t-value exceeded the t-table value at the 0.05 level. These findings suggest that the scramble words technique is an effective and engaging approach for enhancing vocabulary mastery among junior high school students.